Erythropoietin Promotes Infection Resolution and Lowers Antibiotic Requirements in E. coli- and S. aureus-Initiated Infections - Liang, Feihong; Guan, Huiting; Li, Wenhua; Zhang, Xue; Liu, Tingting; Liu, Yu; Mei, Jie; Jiang, Cheng; Zhang, Fengxue; Luo, Bangwei; Zhang, Zhiren (Frontiers in Immunology, 2021)
Endogenous mechanisms underlying bacterial infection resolution are essential for the development of novel therapies for the treatment of inflammation caused by infection without unwanted side effects. Herein, we found that erythropoietin (EPO) promoted the resolution and enhanced antibiotic actions in Escherichia coli (E. coli)- and Staphylococcus aureus (S. aureus)-initiated infections. Levels of peritoneal EPO and macrophage erythropoietin receptor (EPOR) were elevated in self-limited E. coli-initiated peritonitis. Myeloid-specific EPOR-deficient mice exhibited an impaired inflammatory resolution and exogenous EPO enhanced this resolution in self-limited infections. Mechanistically, EPO increased macrophage clearance of bacteria via peroxisome proliferator-activated receptor γ (PPARγ)-induced CD36. Moreover, EPO ameliorated inflammation and increased the actions of ciprofloxacin and vancomycin in resolution-delayed E. coli- and S. aureus-initiated infections. Collectively, macrophage EPO signaling is temporally induced during infections. EPO is anti-phlogistic, increases engulfment, promotes infection resolution, and lowers antibiotic requirements.